The Effect of Flipped Classroom Based STEAM Approach on Mastery of Concepts and Interpersonal Intelligence in Online Learning - Albar, Joni; Wardani, Sri; Sarwi, Sarwi (Universitas Negeri Semarang, 2021)
Innovative learning in the independent learning period from home by utilizing features in online applications in the learning process. The purpose of this study was to analyse the effect of the implementation of the flipped classroom model on concepts mastery and interpersonal intelligence of students. The research used quantitative approach with a quasi-experimental design non-equivalent control group design. The population in this study were 5th grade. The sample were 100 students consisting of four classes. Two experimental classes were given flipped classroom and STEM approach and two control classes were given reguler learning. The samples were chosen with sampling purposive technique. Data collection techniques used test techniques (multiple choice questions) and non-test (observation sheets, questionnaires, interviews, documentation). Data analysis techniques are prerequisite test, one-way ANOVA test and hypothesis t-test. The results of the average research test in the experimental class of concept understanding were 89.52 and interpersonal intelligence was 85.64, while in the control class, understanding of concepts was 77.08 and interpersonal intelligence was 64.74. Based on these findings, it can be concluded that there are significant effects and differences using the STEAM approach-based flipped classroom model in online mode to improve mastery concepts and interpersonal intelligence of students.